NEEDS ANALYSIS OF ENGLISH MATERIAL FOR 10TH GRADE STUDENTS IN OFFICE AUTOMATION AND GOVERNANCE DEPARTMENT - Ainan Salsabilla; Santi Andriyani; Andra Andriawan; Meli Indah Sugiarti (Universitas Islam Lamongan, 2022)
Vocational High School (VHS) is formal education that organizes vocational education at the secondary education level. Learning English at the VHS level is categorized as English for Special Purposes (ESP) which means that English material is expected to meet the students' needs according to their majors. However, many students still have low English proficiency. This study aims to determine the English needs of tenth-grade students majoring in Office Automation and Governance. This study used a descriptive qualitative method. The data were obtained using English tests, questionnaires, and interviews as the instruments. Respondents in this study were tenth-grade students majoring in Office Automation and Governance. The results showed that 1) Lack of innovation and creativity in the teaching materials used by students 2) The materials in the textbooks were not appropriate with the needs of students in the Office Automation and Governance department.Keywords: Needs analysis, English teaching materials, department of office automation and governance